Effective Training Improves Disaster Response. Issue 1 (19th January 2022) - Adams, Hunter; Southard, Mark; Forbes, Steven; Leinweber, Butch; Nix, Daniel K.
Abstract : Preparedness training and continuity‐of‐operations plans helped a Texas water utility's staff keep mission‐essential functions going and water flowing during 2021's record‐breaking winter storm.